2022
DOI: 10.1186/s41983-021-00443-9
|View full text |Cite
|
Sign up to set email alerts
|

Venous and arterial cerebral thrombosis: a COVID-19 dual pathology and single possible etiology—a case report

Abstract: Background Corona virus disease of the year 2019 (COVID-19) is still devastating the world for more than 19 months since its declaration as a pandemic by world health organization. Its manifestations does not stand at respiratory system but involves other body systems including central nervous system and its vasculature. In the following case report, cerebral venous and arterial thrombosis is detected in a case just in convalescence from COVID-19 with still detected positive IgM. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(6 citation statements)
references
References 11 publications
(10 reference statements)
1
4
1
Order By: Relevance
“…All patients reported by Kananeh et al had moderate to critical COVID-19 symptoms, requiring ICU admission, and significantly elevated D-dimer levels. This is also consistent with the reports of Malentacchi et al and Roushdy et al, who reported impaired coagulation profiles and elevated D-dimer levels in their patients with moderate to critical SARS-CoV-2 infections and concurrent arterial and cerebral venous thromboses [1,6]. However, our patient had no fever, and his inflammatory markers, platelet count, D-dimer level, and coagulation profile were within the normal range.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…All patients reported by Kananeh et al had moderate to critical COVID-19 symptoms, requiring ICU admission, and significantly elevated D-dimer levels. This is also consistent with the reports of Malentacchi et al and Roushdy et al, who reported impaired coagulation profiles and elevated D-dimer levels in their patients with moderate to critical SARS-CoV-2 infections and concurrent arterial and cerebral venous thromboses [1,6]. However, our patient had no fever, and his inflammatory markers, platelet count, D-dimer level, and coagulation profile were within the normal range.…”
Section: Discussionsupporting
confidence: 93%
“…Our case is the first reported case of concurrent arterial stroke and cerebral venous thrombosis associated with SARS-CoV-2 infection in Singapore and, as far as we know, the fourth reported case worldwide. [1,5,6], all patients showed significant neurological deficits including coma [1], pyramidal signs such as positive Babinski sign [1], weakness [5], ataxia [5], and seizures [6]. These findings differ from our patient, who had only encephalopathy without other significant neurological symptoms and focal deficits.…”
Section: Discussioncontrasting
confidence: 78%
See 2 more Smart Citations
“…Neurovascular complications of SARS-CoV-2 whether in the form of ischemic strokes or hemorrhagic ones and whether arterial or venous are very common and are reported with mild, moderate, or severe forms of SARS-CoV-2 [39,40].…”
Section: Neuropsychiatric Aspects Of Sars-cov-2 and Mpxmentioning
confidence: 99%